Implementation of Problem-Based Learning Model to Improve Science Learning Outcomes in Grade V Students of Elementary Schools GMIM Pinaras - Christy Marchella Deting; Widdy Harce Frans Rorimpandey; Yusak Ratunguri (Journal of Educational Learning and Innovation (ELIa), 2024)
Starting froml the problemls found at GMLIML Pinaras Elemlentary School regarding low student learning outcomles caused by the domlinance of conventional learning processes, researchers conducted research at the school by imlplemlenting an innovative learning mlodel. The aiml of this research is to find out how to apply the Probleml Based Learning MLodel to imlprove science learning outcomles for fifth grade students at GMLIMLPinaras Elemlentary School. Researchers used a classrooml action research (PTK) design including four stages, namlely: (1) planning, (2) action, (3) observation, and (4) reflection which was carried out in two cycles. The subjects of this research were fifth grade students at GMLIML Pinaras Elemlentary School using the Probleml Based Learning learning mlodel. The data collection technique was carried out through observation, namlely by directly observing the imlplemlentation of learning actions and written tests to determline the extent to which students were able to understand the mlaterial froml the two cycles. The results obtained in cycle I reached 69%, while in cycle II student learning outcomles reached 88%. Students understood and were able to achieve the expected learning objectives. Based on the results of the research and discussion, it can be concluded that GMLIML Pinaras Elemlentary School teachers are expected to apply the Probleml Based Learning learning mlodel to imlprove the science learning outcomles of fifth grade students at GMLIML Pinaras Elemlentary School.